A randomized clinical trial of group and individual Cognitive-Behavioral Therapy approaches for Social Anxiety Disorder - Neufeld, Carmem Beatriz (Int J Clin Health Psychol, 2020)
To compare the effectiveness of two Cognitive-Behavioral Therapy (CBT) interventions—an individual and a group intervention—in Social Anxiety Disorder therapy. We compared the two treatment groups against a waitlist condition in a randomized clinical trial with 86 young adults. The individual CBT intervention was Trial-Based Cognitive Therapy (TBCT) developed by De-Oliveira, a novel technique in which the therapist engages the patient in a simulated judicial trial with the goal of identifying and changing core dysfunctional beliefs. The group intervention consisted of exposition therapy based on the Hofmann and Otto protocol (Group CBT) to restructure negative and dysfunctional cognitions regarding social situations. Both interventions reduced psychiatric symptoms from pre- to post-test and primary social anxiety and depression symptoms relative to waitlist controls. The interventions were recently introduced in Brazil, and this is the first randomized control trial to compare TBCT and this Group CBT, which were effective in assessing changes in social anxiety symptoms as well as co-occurring psychiatric symptoms.